2015
DOI: 10.1002/cbf.3105
|View full text |Cite
|
Sign up to set email alerts
|

JNK and NFκB dependence of apoptosis induced by vinblastine in human acute promyelocytic leukaemia cells

Abstract: The relationship between the mitogen-activated protein kinase response, nuclear factor-κB (NFκB) expression and the apoptosis in human acute promyelocytic leukaemia NB4 cells treated with vinblastine was investigated in this work. Cell viability, subdiploid DNA and cell cycle were analysed by propidium iodide permeability and flow cytometry analyses. Apoptosis was determined by annexin V-Fluorescein isothiocyanate assays. Western-blot analysis was used for determination of expression levels of apoptotic factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
(135 reference statements)
0
4
0
Order By: Relevance
“…Most important signaling pathways are controlled by PI3K, Akt, and the mammalian target of rapamycin (mTOR) (Lefranc and Kiss, 2006). Tumor cell death induced by anticancer drugs is also regulated by various other signaling molecules, including JNK, Erk, c-myc, and NF-kB (Tashiro et al ., 1998; Fan et al ., 2000; Stadheim et al ., 2001; Bressin et al ., 2006; Calvino et al ., 2015). Curcumin activates the P53 signaling pathway by up-regulating P53 and P21, which also inhibit the PI3K pathway by down-regulating PI3K, p-Akt, and p-mTOR (Fu et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Most important signaling pathways are controlled by PI3K, Akt, and the mammalian target of rapamycin (mTOR) (Lefranc and Kiss, 2006). Tumor cell death induced by anticancer drugs is also regulated by various other signaling molecules, including JNK, Erk, c-myc, and NF-kB (Tashiro et al ., 1998; Fan et al ., 2000; Stadheim et al ., 2001; Bressin et al ., 2006; Calvino et al ., 2015). Curcumin activates the P53 signaling pathway by up-regulating P53 and P21, which also inhibit the PI3K pathway by down-regulating PI3K, p-Akt, and p-mTOR (Fu et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In a study, the mechanism of anticancer effect of vinblastine on human acute promyelocytic leukemia NB4 cells was reported, and it was found that vinblastine could induce an apoptotic response by downregulating NF-κB expression, sustaining JNK activation, and finally triggering caspase cascade. In addition, it will also cause changes in p53 and DNA fragmentation [ 124 ]. Moreover, hapalindole H (Hap H), extracted from Fischerella muscicola with a median effective concentration (EC 50 ) value of 20 nM, induced toxicity in the PC-3 prostate cancer cells, and it showed potential NF-ĸB p65 inhibitory activity on PC-3 cells, and this inhibition would lead to apoptotic cell death.…”
Section: Targeting Apoptotic Signaling Pathways With Indole Alkaloids...mentioning
confidence: 99%
“…An example of such a drug is vinblastine, which binds to tubulin and blocks the formation of microtubules, thus inhibiting cell division [ 37 ]. It also shows a pro-apoptotic effect [ 9 , 38 , 39 ] and induces changes in the lysosomal compartment [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%